Examining e-commerce user’s switching intention through an extended push-pull-mooring model - Yuliani, Irma; Nursalam, Annisa; Azizah, Siti Nur; Berakon, Izra (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This study investigates the determinants of Indonesian e-commerce users’ intention toward productive digital behavior using the push–pull–mooring (PPM) model. It further integrates the Homo Islamicus perspective, the technology acceptance model (TAM), and the marketing mix to provide a more comprehensive explanation of this behavioral transition.Methodology – Primary data were collected from 231 Indonesian e-commerce users through an online survey using purposive sampling method. The eligible respondents were individuals who had actively engaged in online shopping. The proposed model was evaluated using a two-stage partial least squares structural equation modeling (PLS-SEM) approach.Findings – The results indicate that push factors, represented by impulse buying and Homo Islamicus attributes, do not significantly explain the switching intention toward productive digital behavior. In contrast, pull factors, including perceived usefulness, perceived ease of use, attitude toward e-commerce, and the marketing mix, significantly influenced switching intention. Mooring factors, including risk propensity, tolerance of ambiguity, and perceived educational support, also positively influenced switching intention.Implications – Encouraging productive digital behavior requires more than just reducing consumptive tendencies. Policymakers and e-commerce platform providers should strengthen digital entrepreneurship education, mentoring, and risk management support to enhance users’ readiness for productive digital activities.Originality – Previous e-commerce studies have primarily focused on purchase intention, online shopping adoption and impulse buying. This study extends the PPM model by explaining users’ switching intention from consumptive to productive digital behavior in the Indonesian e-commerce ecosystem.